Análisis espacial del impacto ambiental causado por el desarrollo de infraestructura vial en áreas sensibles del sur del Ecuador - Quezada Pardo, Ana del Cisne (2014)
This study focuses on the spatial analysis of the environmental impacts caused by the development of road infrastructure Saraguro- Yacuambi, located on a sensitive natural area in south of Ecuador dominated by paramo, lagoons and streams. For this study through the application of the methodology of the Spatial Impact Assessment Methodology (SIAM) and the use of Geographical Information Systems (GIS) was evaluated the environmental impacts caused by the construction of the road Saraguro –Yacuambi to three scales of analysis, this methodology is based on three steps: 1) Scoping 2) Prediction and classification of environmental descriptors and 3) Calculation of indices and impact indicators. The results show that through aggregation of impacts the paramo was the greatest environmental component affected. This result in part validate the application of SIAM for environmental impact studies, however, the initial phases of this methodology show a high degree of difficulty by substantial basis information required for this execution, thus delaying the results.